قلق مرضى الذبحة الصدرية في محافظات غزة وعلاقته بجودة الحياة - الهمص, عبد الفتاح (جامعة الوادي University of Eloued, 2017)
هدفت الدراسة إلى معرفة علاقة قلق مرضى الذبحة الصدرية في محافظات غزة بجودة الحياة لدى عينة الدراسة والمكونة من (300) مريض ومريضة، من مرضى الذبحة الصدرية بمحافظات غزة واستخدمت الدراسة استبانة قلق الذبحة الصدرية، واستبانة جودة الحياة، من إعداد: الباحث، كما استخدمت الدراسة المنهج الوصفي الأسلوب التحليلي، وخلصت الدراسة إلى مجموعة من النتائج أهمها: خوف مرضى الذبحة الصدرية من مرضهم، واعتقادهم أن الموت قادم في أي لحظة دون سابق إنذار وظنهم بعجز الطب عن إيجاد الدواء الشافي لهم، وكذلك كان مستوى جودة الحياة إيجابي لدى مرضى الذبحة الصدرية في محافظات غزة، وهذا نابع من استسلام المرضى وأنهم آمنوا بقدرهم، مع مساعدة أسرهم، وأقرانهم لهم في تكيفهم مع مرضهم، وكذلك خوف مرضى الذبحة الصدرية من وسطية العمر وهي أخطر المراحل العمرية التي يمر بها الإنسان في حياته. كما كان هناك تكيف أصحاب الفئة العمرية (50 سنة فما فوق) مع مرضهم نتيجة اقترابهم من سن اليأس والعجز مقارنة بغيرهم ممن هم أقل عمراً. This study aimed to investigate the relationship of anxiety angina patients in the provinces of Gaza, quality of life, the study sample consisting of (300) patients and sick, of angina patients the provinces of Gaza, the study used a questionnaire concern angina, and to identify the quality of life of the preparation: Researcher and study used a descriptive analytical method, the study found a range of results, including: fear of angina patients of their illness, and the belief that death is coming at any moment without warning, and they believe the inability of medicine to find a panacea for them, as well as the level of quality of life positive in patients with angina pectoris in the provinces of Gaza, and this stems from the surrender of patients and they believed-worth, with the help of their families, and their peers for them in their coping with their illness, as well as the fear of angina patients of average age and is the most dangerous stages of life experienced by the man in his life. There was also adaptable age group owners (50 years and older) with their illness as a result they approach menopause, disability, compared with others who are less older.
مقال
Keywords: قلق؛ الذبحة الصدرية؛ جودة الحياة; anxiety; angina; quality of lif